Human biliary tree stem/progenitor cells immunomodulation: Role of hepatocyte growth factor. Issue 5 (16th August 2016) - Maraldi, Tullia; Guida, Marianna; Beretti, Francesca; Resca, Elisa; Carpino, Guido; Cardinale, Vincenzo; Gentile, Raffaele; Ardizzoni, Andrea; Murgia, Alba; Alvaro, Domenico; Gaudio, Eugenio; De Pol, Anto
Abstract : Aim: Human biliary tree stem/progenitor cells (hBTSC) are multipotent epithelial stem cells with the potential for allogenic transplant in liver, biliary tree, and pancreatic diseases. Human mesenchymal stem cells, but also epithelial stem cells, are able to modulate immune responses with different types of secretion molecules. Methods: The initial aim of the present study was to develop for the first time a culture protocol in order to expand hBTSC in vitro through passages, allowing to maintain a similar stem cell and secretome profile. Furthermore, we investigated the secretome profile of the hBTSC to assess the production of molecules capable of affecting immune feedback. Results: We found that hepatocyte growth factor produced by hBTSC exerts its cytoprotective role inducing apoptosis in human immune cells, such as lymphocytes. Conclusions: The present study, therefore, supports the hypothesis that hBTSC can be useful for the purpose of regenerative medicine, as they can be banked and expanded, and they can secrete immunoregulatory factors.